ANALISIS BAGI HASIL, KUALITAS PELAYANAN, DAN MINAT NASABAH DALAM MENGGUNAKAN PRODUK DEPOSITO SYARIAH - Muhammad Ramadhan; Zaki Mubarak; Lisda Aisyah (Fakultas Ekonomi Dan Bisnis Islam IAIN Metro, 2022)
There was an increase in the number of deposit accounts that were not in line with fluctuations in the number of Islamic deposit funds in the 2018-2020 period. This study aims to find out and analyze the effect of profit sharing and service quality on customer interest in using sharia deposit products at PT Bank Tabungan Negara KCS Banjarmasin. Field research with a quantitative descriptive approach, this study uses multiple linear regression analysis with the IBM SPSS Statistics 22 program. The regression results obtained the variable of profit sharing and service quality were able to explain the variable of customer interest by 20.3%, and the remaining 79.7% was explained by other variables outside the study. In the t-test, the profit sharing variable has a significant effect on customer interest while the F test, the profit sharing variable and service quality affect customer interest. Until, the variable of service quality also has a significant effect on customer interest.